Emergency Surgery and Cardiac Devices - Zecchin, Massimo; Rivetti, Luigi; Sinagra, Gianfranco; Merlo, Marco; Aleksova, Aneta (The Arrhythmic Patient in the Emergency Department, 2016)
Because of the increasing number of patients treated with cardiac implantable electronic devices (CIED), as pacemakers (PM) or implantable cardioverter-defibrillators (ICD), their management in case of emergent surgery is becoming a scenario frequently observed in the clinical practice. A deep knowledge of the CIED and how they work is rare, not only among non-cardiologist physicians facing emergencies but, not infrequently, even among consultant cardiologists. In the emergency setting, the presence of the CIED can be completely ignored or, on the contrary, causes unnecessary delays of the proper treatment of the emergency. Some notions about the management of patients with CIED who need emergent/urgent surgery are provided, starting from general to more detailed information both directed to first-line physicians, who must face the emergency (surgeons, anesthesiologists, and emergency physicians), and the consultant cardiologist, who should consider the relationship between the specific patients and the CIED. Finally, a practical algorithm, considering most guidelines and some specific issues of the emergency, is proposed.